Utilization of peat soil into peat coagulant and its optimization in aquaculture using Box‑Behnken design and molecular docking for fish growth and sustainable water quality - Helal Uddin, A.B.M.; Ahmed, Qamar Uddin; Azmi, Syed Najmul Hejaz; Nasir Al Rawahi, Wafa Aqib; Al Hoqani, Umaima; Al Ajmi, Atheer Talib; Sah, Pankaj; Bhat, Aamir Hussain; Hussain, Mohammed Zakir; Rahman, Nafisur; Mia, Md. Abdur Rashid (Springer Nature, 2025)
Peat coagulant was synthesized using local peat soil and ethylene diamine to enhance water quality and improve the growth of Tilapia (Oreochromis niloticus) in freshwater aquaculture. The application of this coagulant was successfully optimized using the Box-Behnken design model. The synthesized coagulant significantly improved water quality by reducing chemical oxygen demand (COD), phosphate ion concentration, and unionized ammonia nitrogen. The pH of the water was improved and shifted from 7.72 to 7.06. The optimal conditions for maximizing fish growth were identified as 20 L of aerated water, 2.5% fish feed per average fish weight, and 0.3 mL L −1 peat coagulant, which resulted in a maximum average fish weight increase of 18.79% ± 0.3%. Additionally, a theoretical molecular docking study using conserved human arginase enzymes (as validated surrogate models; a common approach in comparative enzymology and aquaculture bioinformatics) was conducted to model interactions of essential dietary amino acids (arginine, histidine, lysine), highlighting their role in nitrogen metabolism relevant to water quality. This computational insight supports the biological context but is not mechanistically linked to the peat coagulant’s action. The peat coagulant presents a sustainable, fish-safe solution for improving aquaculture water quality. These conditions were successfully applied across various fish populations, validating the consistent growth enhancement. The use of peat coagulant proved to be environmentally beneficial, maintaining nutrient and organic levels while reducing harmful contaminants in the water, making it suitable for aquatic life. This peat coagulant has the potential to serve as a sustainable aquaculture additive for improving aquaculture systems.